The Effects of Implementing a Task-Based Approach to Enhance Student Engagement in a 10th Grade English Class at I.E. Doce de Octubre (2016)
ABSTRACT: This research project presents the results of the teaching practicum in Licenciatura en Lenguas Extranjeras program at the Universidad de Antioquia. Disengagement has become a staple in the English classes where students felt powerless to decide what they wanted to learn. The project shows the effects of the implementation of task based activities to enhance tenth graders emotional engagement in language learning (English) at I.E Doce de Octubre, Medellin. The project was conducted with 31 students from this public institution, from February to November 2016. Data collection techniques included interviews, surveys and journals provided by the CT and students through comments and reflections. Results showed that after the implementation of the action plan, student needs, interests and emotional engagement were enhanced, improving their academic results and motivation.